What and How Can We Learn from the Quran? A Critical Rationalist Perspective - Paya, Ali (Islamic Studies, 2014)
The aim of this paper is to introduce a critical rationalist approach to studying the Quran. Following a short introduction, I shall introduce the main tenets of critical rationalism with a short account of religion according to this approach. The paper shall then briefly discuss a cluster of related notions, namely, ‘algorithmic compressibility,’ ‘complex systems,’ and ‘logical depth.’ Taking stock from this discussion, the writer argues that the Quran is a complex system with a significant logical depth and that its message can be best understood with a critical rationalist approach. Further, This approach will be analysed vis-a-vis the method of istintaq (interrogation) introduced by ‘Ali b. Abu Talib in Nahj al-Balagah. Finally, some possible criticism to the critical rationalist approach to studying the Quran will be considered.